Analysis of the determinants of anemia in pregnant women in the working area of The Wonggeduku Barat Public Health Center - La Ode Liaumin Azim; Rianti; Murlan; Rasma (Sarana Ilmu Indonesia (salnesia), 2025)
Anemia in pregnant women is a health problem that can cause serious complications for both the mother and the fetus. Anemia prevalence among pregnant women in Indonesia was 48.9% in 2024, while at the Wonggeduku Barat Community Health Center from January to March 2023, the rate was 25.6%. This study aims to analyze the determinants associated with the incidence of anemia in pregnant women in the Wonggeduku Barat Community Health Center working area. This study was an observational analysis with a case-control study design. The sample consisted of 78 pregnant women (39 cases and 39 controls), matched by gestational age in the first, second, and third trimesters. The data were collected through interviews and hemoglobin laboratory tests. Data analysis used the odds ratio test with SPSS Statistics version 25, with a 95% confidence level. Data analysis was performed using the Odds Ratio test with SPSS version 25 and a 95% confidence level. The statistical test results showed that compliance with iron tablet consumption (OR=3.053) and dietary patterns (OR=2.970). It was concluded that iron tablet consumption and dietary patterns were risk factors for anemia in pregnant women. Therefore, it was recommended that access to better health services be improved, and that education on the importance of a nutritious diet for pregnant women in preventing anemia be provided.